PENGARUH PERMAINAN HALANG RINTANG TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Nurazianti Nurazianti; Wusono Indarto; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of the obstacle game towards gross motor skills of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru. Research using experimental method with pretest posttest control group design. Population in this study were children aged 5-6 years, amounting to 90 children and the sample used in this study were 30 children divided into two classes, experimental class and control class. The data collection technique used is observation. Technique of data analysis using t-test by using program of SPSS 20. The research hypothesis that there is the effect of obstacle game towards gross motor skills of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru. Based on data analysis known tcount = 19,778> t table = 2.086 with Sig. (2-tailed) = 0.000. because Sig <0,05 can be concluded that there is difference in gross motor skills before and after the use of obstacle game. Can be interpreted that there is effect of obstacle game towards gross motor skills of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru which significant equal 68.36%Keywords: Gross Motor Skills, Obstacle Game